Adrenal Metastases as Sanctuary Sites in Advanced Renal Cancer (Journal of Kidney Cancer, 2020)
Involvement of the adrenal gland in kidney cancer represents a unique site of metastasis with a distinct clinical course. The cases are typically resistant to immune therapy and need local therapy management. A case series of patients with adrenal metastases was reviewed to highlight the nuances of clinical course and therapy. We reviewed renal cancer carcinoma (RCC) cases with adrenal metastases at Karmanos Cancer Center, Detroit MI. Medical records were reviewed to collect relevant case information. Next-generation sequencing, tumor mutation burden testing, and programmed death ligand biomarkers were evaluated in five cases. Twelve cases were reviewed; all were males with a median age of 49.5 years. Three patients presented with adrenal metastases only and were treated with local therapy. Three received interleukin-2 (IL-2). One patient relapsed with bilateral adrenal lesions after 11 years of remission, post-IL-2 therapy. Five cases received immune checkpoint inhibitor (ICI) and one received antivascular therapy. ICI therapy was followed by ablation of residual adrenal metastases in three patients. Genomic profiling was available in five cases. All were BAP1 and PD-L1 negative. Pathogenic mutations in PBRM1, SETD2, and VHL were noted. All patients with residual adrenal metastases responded to antivascular therapies or to local ablation. One patient died 17 years after diagnosis and 11 patients are alive at a median follow-up of 9.5 years. Adrenal metastases in RCC have a distinct clinical course. They can represent a sanctuary site of relapse/residual disease following treatment with immune therapy. Management with local therapy can induce durable remissions. Systemic management with antivascular therapies also demonstrated favorable responses. Further investigation should focus on the unique clinical course and optimal management of adrenal metastases in kidney cancer.